SERUM OXIDATIVE STRESS PARAMETERS IN BREAST CANCER IRAQI PATIENTS BEFORE AND AFTER RADIOTHERAPY - Athraa Alkindi; Wisam Kadhum H. Alhashemi; Sabbar Shokry Albayaty (Scholar Express Journals, 2022)
In this study, radiation therapy (RT) effects on some serum oxidant and antioxidant parameters in breast cancer (BC) patients were investigated. Background: RT, which is used to treat cancer, causes molecular damage to living cells by producing reactive oxygen species. Aqueous free radicals (radiation on water) produce the majority of radiation damage to human tissues since they include 80% water. The primary free radicals produced by aqueous radiolysis are (OH, H, eaq – , HO2, H3O+). These free radicals damage DNA, RNA, proteins, membranes, and other biological components, causing cell death. Radiation causes these effects in both malignant and normal cells. Patients and Methods: Sixty BC female patients were involved in this study and received RT at a dose of 40.50 Gray for three weeks, in comparison with a matched (number, mean age, and mean BMI) healthy control group. Blood samples were obtained one day before and after the end of RT from each patient. Serum levels of Malondialdehyde (MDA), Total Serum Bilirubin (TSB), Uric Acid (UA), and Albumin (Alb) were analyzed by full-auto spectrophotometry or ELISA. T-test and a paired t-test were used to compare pre-and post-radiotherapy data with a healthy control group.
Keywords: Antioxidant; Radiotherapy; Oxidative Stress; Breast cancer